Fenomena Pengalaman Pengasuh Anak Korban Kekerasan Fisik di Kota Banda Aceh: Studi Kualitatif - Riani, Eka Oktarina; Said, Devi Elvin; Jauhari, Julianti; Nirwan, Nirwan (Journal Keperawatan, 2024)
Background: Violence against children is a global phenomenon that poses significant challenges to the health care system because it has serious consequences for victims. Purpose: To examine the experiences of caregivers in Banda Aceh who provide assistance to children who have been physically abused. The event under consideration involves perception, adaption reaction, physiological delivery, supporting the child's adaptation process concerning interdependence, and assisting the child's adaptation process concerning self-concept, role, and function.  Methods: This study used a qualitative, phenomenological approach to its investigation. The caregiver serves as the major informant for this study, providing care and meeting the needs of children who are physically abused. Key informants have traits including providing for the everyday needs of the children they live with, living at home with child victims of violence, and effectively communicating their experiences. Interviews and pertinent literature reviews were used to gather research data, which was subsequently analyzed using the Colaizzi. Results: The study's findings are as follows: 1) The caregiver is aware that the child's perception of physical violence is a result of their wrongdoings, 2) The principal caregiver observes the detrimental effects of physical abuse on the kid, 3) The violent child receives physical assistance from the primary caregiver. current physiological requirements by obtaining resources, 4) By offering moral support, the caregiver assists children who experience physical abuse in their self-concept. 5) Using techniques to enhance the child's role function, the caregiver supports children who have experienced physical abuse in this area, and 6) The caregiver seeks counseling support in order to assist children who are physically abused in the area of interdependence. Conclusion: caregivers are capable of improving perception, adaptation reactions, physiological delivery, supporting the child's adaptation process based on interdependence, and helping the child adapt to self-conceptions, roles, and functions.